Benign metastasizing leiomyomas in the lungs: a case study - Wiencek-Weiss, Alina Janina; Bruliński, Krzysztof (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Benign metastasizing leiomyoma (BML) is a rare disease that occurs in middle-aged women with a history of uterine myomas. The most common location of BML is the lungs. We report the case of a 44-year-old obese woman (BMI 45.5) who underwent surgery to remove uterine leiomyomata and then continued to take a drug containing the hormone estradiol for a period of 15 years. Computed tomography chest examinations revealed multiple size nodules of varying size in both lungs. Videothoracoscopy and right thoracotomy was performed, and a few nodules were enucleated from each lobe of the right lung. Postoperative histopathological examination revealed benign metastasizing leiomyoma staining positive for estrogen and progesterone receptors (ER+, PR+). Because of the hormonally dependent cell proliferation, the previously used hormonal drug was discontinued. Treatment with a gonadotropin-releasing hormone analog was included, yielding radiological stabilization of the lung lesions.